Grundvattenkarakterisering med syreisotoper : En fältstudie i Gäddviks vattentäkt i Luleå - Lempinen, Simja (Luleå tekniska universitet, Geovetenskap och miljöteknik, 2019)
Groundwater and artificially recharged groundwater are important sources offreshwater in Sweden. In growing societies an ever larger demand is put onmunicipalities drinking water production facilities. Especially in coastal areas oraquifers that are located below the highest coastal line, there can be ionically strongpaleowaters at greater depths which then risk being pumped up to the municipal watersupply. A common problem for municipal water works is that production wells pumpup ionically strong water, with a high electrical conductivity when the production wellsare stressed at high effect or longer periods of constant pumping. At the waterworks ofGäddvik in Luleå municipality certain wells have shown tendencies of higher electricalconductivities in the produced water, while some wells seem to never produce waterwith higher electrical conductivity, no matter how much they are pumped. Highelectrical conductivities has earlier been assumed to be paleowaters from below theaquifer with great concentrations of chloride, but this is not certain.This work investigates the possibilities of characterizing groundwater by using theoxygen isotopes 16O & 18O as well as main element analysis. In the work a field surveywas performed where groundwater was pumped up from 26 observational wells and 5productional wells at Gäddviks aquifer in Luleå. The samples were analyzed for isotopesof both oxygen and hydrogen as well as the main elements. The results have shown thatit is possible to correlate the heaviest isotopic signatures of oxygen with the highestmeasured values of chloride. This indicates that there is a potential value for identifyingpaleowaters with the help of oxygen isotopes especially when correlated to mainelement data.